STUDY OF LAND COVER CHANGESAGAINST FLOOD ON UPPER CITARUM WATERSHED(CASE STUDY OF UPPER CITARUM RIVER TO CIWIDEY RIVER) - Musthopa Swara, Yuddi
One of the variables that can influence the characteristics of a watershed (DAS) and its hydrology is changes in land use. The population growth in the upstream Citarum Watershed, located in the City and Regency of Bandung, significantly affects changes in land cover in the upstream Citarum Watershed. Bandung, which serves as the capital of West Java Province and is also in the upstream area of the Citarum Watershed, is exposed to significant economic growth, attracting human behavior towards urbanization and leading to increased infrastructure needs such as residential and office areas. This increased demand is the cause of land use conversion from green open spaces to closed areas, such as residential or office areas. The change in land cover reduces the ability to absorb runoff, thereby increasing the water level or causing floods. Hydrological modeling using HEC-HMS will demonstrate the impact of curve number values, time lag, and infiltration values on discharge in the upstream Citarum Watershed in the year 2022, which will be calibrated with the discharge in the Nanjung Watershed. Discharge values, Manning's coefficient, and river geometry are the main parameters in flood modeling using HEC-RAS. The curve number values will be determined based on changes in land cover in the years 1990 and 2022.